INTRACELLULAR Ca2+ HOMEOSTASIS - Kurniawan, Shahdevi Nandar (Malang Neurology Journal, 2015)
Ca2+ signaling functions to regulate many cellular processes. Dynamics of Ca2+ signaling or homeostasis is regulated by the interaction between ON and OFF reactions that control Ca2+ flux in both the plasma membrane and internal organelles such as the endoplasmic reticulum (ER) and mitochondria. External stimuli activate the ON reactions, which include Ca2+ into the cytoplasm either through channels in the plasma membrane or from internal storage like in ER. Most of the cells utilize both channels/sources, but there area few cells using an external or internal source to control certain processes. Most of the Ca entering the cytoplasm adsorbed to the buffer, while a smaller part activate effect or to stimulate cellular processes. Reaction OFF is pumping of cytoplasmic Ca2+ using a combination mechanism of mitochondrial and others. Changes in Ca2+ signal has been detected in various tissues isolated from animals induced into diabetes as well as patients with diabetes. Ca2+ signal interference is also found in sensory neurons of experimental animals with diabetes. Ca2+ signaling is one of the main signaling systems in the cell.